Captivating color: evidence for optimal stimulus design in a polymorphic prey lure. (15th May 2022) - Kemp, Darrell J; Edwards, Will; White, Thomas E
Abstract: Many species – humans included – employ color as an instrument of deception. One intriguing example of this resides in the conspicuous abstract color patterns displayed on the bodies of female orb weaving spiders. These displays increase prey interception rates and thereby function at least as visual lures. Their chromatic properties however vary extensively, both across and within species, with discrete forms often co-existing in the manner of a stable polymorphism. Variation is principally expressed in terms of signal hue (color per se ), but it is unclear how attractiveness scales with this property and if extant morphs are maximally attractive relative to a graded range of potential alternatives. We examined these questions by assessing catch rates among color-manipulated females of the dimorphic jeweled spider Gasteracantha fornicata in their natural webs. The manipulation altered dorsal appearance in a manner akin to adding six new variants of their existing white/yellow phenotypes. This magnified the natural variation in stimulus hue independently of chroma (saturation) across a range spanning most of the color spectrum. Catch rate varied across treatments in simple accordance with how greatly stimulus hue deviated from either of the two extant spider phenotypes. Predictions based on fly-perceived chromatic and achromatic background contrast were clearly unsupported despite dipterans constituting ~60 % of identifiable prey. This study supports the importance of signal coloration per se in G. fornicata and suggests that extant lure phenotypes reside in a broadly optimal spectral range for stimulating their aggregate prey community. Abstract : Color matters if you are a spider seeking to lure a meal. We use a novel method of manipulating the appearance of wild orb-web spiders to demonstrate that spectral quality, that is, color per-se, determines their success in capturing prey. The study species naturally occurs in two different forms, white and yellow, and we also show that these correspond to maximal predicted prey attractiveness over the manipulated range of color variation.